2022
DOI: 10.1111/ina.13156
|View full text |Cite
|
Sign up to set email alerts
|

Moldy odor from air conditioners in the residences of Japanese participants with and without asthma

Abstract: Fungi are a major environmental allergen. 1 Exposure and sensitization to environmental fungi are associated with asthma onset, severity, and exacerbation. 2 Furthermore, fungi pose a risk for the development of more severe conditions such as allergic bronchopulmonary aspergillosis/mycosis (ABPA/ABPM). An estimation of the global burden suggested that ABPA develops in approximately five million patients with asthma worldwide. 3 As more time is spent at home in the era of the coronavirus disease 2019 (COVID-19)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Airborne fungal concentration increases from 40-920 to 5,500-100,000 colony-forming units•m -3 immediately after the operation of household ACs [17]. In our online survey, 37.1% of 1,006 Japanese participants reported a moldy odor from household ACs indicating fungal contamination [20]. ACs contaminated with fungi can impact the health outcomes of patients with allergic fungal airway diseases.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Airborne fungal concentration increases from 40-920 to 5,500-100,000 colony-forming units•m -3 immediately after the operation of household ACs [17]. In our online survey, 37.1% of 1,006 Japanese participants reported a moldy odor from household ACs indicating fungal contamination [20]. ACs contaminated with fungi can impact the health outcomes of patients with allergic fungal airway diseases.…”
Section: Introductionmentioning
confidence: 75%
“…Fungal abundance and composition were examined in the ACs of living rooms in the present study because Japanese residences are predominantly equipped with ACs in the living room (90.2%), followed by the bedroom (50.1%) [20]. Furthermore, a Canadian study reported that airborne spore concentrations were the highest in living rooms [31].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The apartment interiors were maintained at a room temperature of 24 °C using air conditioning, and a household humidifier was installed in the living room for humidification (Zhao et al, 2018). During the operation of the ventilation system, the indoor relative humidity did not reach 50% with a single household humidifier (Okada et al, 2022). However, considering using one humidifier per unit is common, only one humidifier was installed, and the humidification amount was set to the maximum.…”
Section: Alternating Current Typementioning
confidence: 99%